The Place of Gulf Basin Energy Resources in EU Energy Security - Sarkhanov, Teymur; Muradzada, Imangulu (International Journal of Energy Economics and Policy, 2023)
The article discusses the importance of Gulf Basin energy resources in ensuring energy security for the European Union (EU). The Gulf region is a major source of oil and gas for the EU, which is heavily dependent on imports to meet its energy needs. The article highlights the various challenges faced by the EU in securing its energy supply from the Gulf region, including geopolitical tensions, price volatility, and the need to diversify its energy mix. It also discusses the role of renewable energy sources in reducing the EU’s dependence on Gulf energy resources. Overall, the article argues that the Gulf Basin will continue to play a critical role in meeting the EU’s energy needs, and that efforts must be made to ensure the security and stability of this energy supply. However, the article also suggests that the EU should explore alternative sources of energy and reduce its reliance on Gulf energy resources. It notes that the EU has made significant progress in promoting renewable energy and energy efficiency, and that these efforts should be continued and expanded. Another important point raised in the article is the need for cooperation between the EU and Gulf countries to ensure energy security. The EU must engage in dialogue with these countries to address common challenges and promote mutual interests. In conclusion, the article provides a comprehensive overview of the role of Gulf Basin energy resources in EU energy security. While acknowledging the importance of these resources, it also emphasizes the need for diversification and cooperation to ensure a stable and sustainable energy supply.